Knee osteoarthritis patients assessed during walking for ankle inversion movement discrimination sensitivity - Huang, Yanfeng; Li, Wanjuan; Shi, Xiaojian; Wang, Wenchao; Xu, Chengshuo; Adams, Roger David; Lyu, Jie; Han, Jia; He, Yaohua (Frontiers in Bioengineering and Biotechnology, 2024)
Background: Knee osteoarthritis (KOA) is a common musculoskeletal condition that affects dynamic balance control and increases the risk of falling during walking. However, the mechanisms underlying this are still unclear. Diminished ankle proprioception during walking has been found to be related to fear of falling in older adults, with a gender difference in incidence of falling. This study aimed to determine 1) whether ankle inversion proprioceptive acuity during walking is impaired in patients with KOA; and 2) whether there is any difference between genders.Methods: Thirty-two patients with KOA (F:M=17:15, Median age=52.5, BMI=22.3± 3.0) and 34 healthy controls without KOA (HC) (F:M=17:17; median age=49.0, BMI=22.5±2.7) were recruited. In patients with KOA, ankle inversion proprioceptive acuity was measured on the affected side using the ankle inversion discrimination apparatus for walking (AIDAW), whilst HC were assessed on a randomly selected side. Two-way (2*2) analysis of variance (ANOVA) was performed to determine the main effects and interaction between gender and KOA condition.Results: Two-way ANOVA showed a significant KOA main effect (F=26.6, p<0.001, ƞ p 2 =0.3) whereby AIDW scores during walking for individuals with KOA were significantly lower than those without KOA (KOA vs HC: 0.746 ±0.057 vs 0.807±0.035). There was neither a gender main effect nor interaction (both p>0.05) Conclusion: Individuals with KOA demonstrated lower ankle proprioception scores during walking compared to their healthy counterparts, with a similar level of impairment in ankle proprioceptive acuity between male and female patients. A low score may contribute to an increased risk of falling in the KOA population. The current findings suggest the need for global concern about lower limb proprioception in the clinical management of KOA.